Australian dentists' knowledge and attitude towards HPV infection - Ms Beata Rumianek; Dr Ewa Siedlecka; Dr Shailendra Sawleshwarkar; A/Prof Shilpi Ajwani (Elsevier, 2023)
Aim or Purpose: As the incidence of oropharyngeal squamous cell carcinoma (OPSCC) is increasing, knowledge of OPSCC risk factors, such as HPV infection and sexual behaviour, is important for dental clinicians and patients, and this study aimed to determine the attitude, knowledge and behaviour of dentists regarding HPV and OPSCC. Materials and Methods: This cross-sectional quantitative study, approved by the University of Sydney Ethics Committee, was conducted between 2020-2021 and involved Australian dentists responding to an online survey. The questionnaire link was distributed through the Australian Dental Association publications, magazines, Facebook and ADX conference. Data were evaluated via SPSS using a combination of univariate and bivariate analyses, and a p-value ≤ 0.05 was considered significant. Results: Of 114 participants, 58.8% were from NSW/ACT, 55.3% were female, 52.6% were from private practice, and 47.4% had ≥16 years of experience. Those who practised for 16+ years (79.6%) had more knowledge of the association between oral HPV and OPSCC, and dentists who accessed information through the university, colleagues or television were less knowledgeable about HPV/OPSCC than those who attended continuing education courses. While the majority agreed that oral HPV testing would be beneficial for early OPSCC diagnosis (79.8%) and patient education (64.0%), a large proportion (70.1%) felt uncomfortable discussing oral sex as a cancer prevention method, and 51.8% had never received sexual health education. Conclusions: Dental practitioners understand the importance and are ideally placed to discuss HPV and the risk of OPSCC, but additional training is required. Continuing education through ADA courses, publications, conferences, seminars, and dental and medical journals provided the updated information most effectively.